Accurate Modelling of Group Electrostatic Potential and Distributed Polarizability in Dipeptides. Issue 19 (2nd October 2020) - Jabłuszewska, Angelika; Krawczuk, Anna; Dos Santos, Leonardo H. R.; Macchi, Piero
Abstract : The Front Cover describes reconstruction of atomic and functional‐group electrostatic potentials and distributed polarizabilities in dipeptides. Such defined properties are transferable between similar systems and help predicting electric properties of macromolecules from their structural subunits. More information can be found in the Article by A. Krawczuk and co‐workers .